Thank you for coming to my TED talk : a teen guide to great public speaking - Anderson, Chris, 1957 January 14-; Oberweger, Lorin (Houghton Mifflin Harcourt, 2020)
Offers teenage students lessons on learning to be confident and engaging when public speaking, based off of lessons the author has learned from being the Head of TED and listening to many TED Talks. Discusses preparation pointers, visual cues, ideas for stopping pre-talk jitters, and how to avoid procrastination.